A flexible enzyme-electrode sensor with cylindrical working electrode modified with a 3D nanostructure for implantable continuous glucose monitoring. Issue 23 (30th October 2018) - Pu, Zhihua; Tu, Jiaan; Han, Ruixue; Zhang, Xingguo; Wu, Jianwei; Fang, Chao; Wu, Hao; Zhang, Xiaoli; Yu, Haixia; Li, Dachao
Abstract : A novel flexible enzyme-electrode sensor was fabricated with a big cylindrical working electrode which, cooperating with the surface-modified 3D nanostructure, significantly improved the sensitivity. Abstract : A novel cylindrical flexible enzyme-electrode sensor was fabricated with a bigger working electrode (WE) surface than the traditional pin-like one for implantable continuous glucose monitoring. On the WE surface, a 3D nanostructure consisting of graphene and platinum nanoparticles was constructed to enhance the sensitivity; in conjunction with the bigger WE, this nanostructure enabled hypoglycemia detection, which is still a big challenge in clinics. The cylindrical sensor was fabricated by rotated inkjet printing which enabled direct patterning of microstructures on a curved surface, thus overcoming the restriction of the traditional planar micromachining by photolithography. Specifically, the cylindrical substrate (polyetheretherketone, PEEK) was modified by (3-aminopropyl) trimethoxysilane and (3-mercaptopropyl) trimethoxysilane to facilitate surface wettability, which discourages the coalescence of adjacent droplets, and to facilitate the adhesion of metals to PEEK in order to construct robust electrodes. A synchronous heating method was used to evaporate the solvent of the droplets quickly to prevent them from running along the cylindrical surface, which affects the formation of the printed electrode significantly. In vitro experimental results showed that the proposed sensor was able to detect the glucose concentration ranging from 0 to 570 mg dL −1 which demonstrated its capability for physiological glucose detection. In vivo experiments were conducted with rats, and the measurement results recorded using the implanted cylindrical sensor showed great compliance to those recorded using a commercial glucometer which exhibited the viability of the proposed sensor for implantable continuous glucose monitoring, even under the hypoglycemic conditions.